Liquid pump-enabled hydrogen refueling system for medium and heavy duty fuel cell vehicles: Station design and technoeconomic assessment. (19th July 2022) - Ku, Anthony Y.; Reddi, Krishna; Elgowainy, Amgad; McRobie, Jordan; Li, Jimmy
Abstract: Recent progress in submerged liquid hydrogen (LH2 ) cryopump technology development offers improved hydrogen fueling performance at a reduced cost in medium- and heavy-duty (MDV and HDV) fuel cell vehicle refueling applications at 35 MPa pressure, compared to fueling via gas compression. In this paper, we evaluate the fueling cost associated with cryopump-based refueling stations for different MDV and HDV hydrogen demand profiles. We adapt the Heavy Duty Refueling Station Analysis Model (HDRSAM) tool to analyze the submerged cryopump case, and compare the estimated fuel dispensing costs of stations supplied with LH2 for fueling Class 4 delivery van (MDV), public transit bus (HDV), and Class 8 truck (HDV) fleets using cryopumps relative to station designs. A sensitivity analysis around upstream costs illustrates the trade-offs associated with H2 production from onsite electrolysis versus central LH2 production and delivery. Our results indicate that LH2 cryopump-based stations become more economically attractive as the total station capacity (kg dispensed per day) and hourly demand (vehicles per hour) increase. Depending on the use case, savings relative to next best options range from about 5% up to 44% in dispensed costs, with more favorable economics at larger stations with high utilization. Highlights: New submerged cryopumps offer improved performance for hydrogen refueling stations. Economic analysis tools have been adapted to model stations with new cryopump. Cost is mainly driven by hourly fueling demand and station daily capacity. Liquid pump-based stations are most attractive at larger stations with high utilization. Up to 44% reduction in dispensing cost is possible with new cryopump for heavy-duty truck stations.